2019
DOI: 10.3390/ijerph16101823
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Source and Risk Assessment of Heavy Metal(oid)s in Water, Sediments, and Corbicula Fluminea of Xijiang River, China

Abstract: A total of 43 water and sediment samples, and 34 Corbicula fluminea samples were collected in Xijiang River in southern China to determine the spatial distribution and sources of 12 metals/metalloids (V, Co, Cr, Ni, Cu, Mn, Zn, Cd, Pb, As, Sb, and Tl) and to assess the pollution levels and ecological risks of the pollutants. The results showed that the levels of the metals/metalloids (except for Tl) in the river water from almost all of the sampling sites met the Chinese national surface water quality standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…The prevalence of Pb in water resources stems from the use of leaded gasoline and lead-based paints and thoughtless dumping of dead car lead acid accumulators [63][64][65]. Lead is a toxic nonessential trace metal and the concentrations found in R. Nyamwamba may be harmful to humans when ingested [66].…”
Section: Seasonal Variations In Physicochemical Parameters Of Water I...mentioning
confidence: 99%
“…The prevalence of Pb in water resources stems from the use of leaded gasoline and lead-based paints and thoughtless dumping of dead car lead acid accumulators [63][64][65]. Lead is a toxic nonessential trace metal and the concentrations found in R. Nyamwamba may be harmful to humans when ingested [66].…”
Section: Seasonal Variations In Physicochemical Parameters Of Water I...mentioning
confidence: 99%
“…This has been demonstrated by the Environment Agency of England and Wales in the rivers that flow through old mining districts in the United Kingdom, where after more than 4000 years, the rivers have been contaminated by lead, zinc and copper and many other metals and metalloids, including iron, tin, arsenic and silver, from dumpsites and tailings dams that have contributed solid contaminants to live-bed channels and floodplains of the rivers for decades after their closure [2,[4][5][6]. This has been equally evident in other mining districts of the world [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The effect is manifested with greater intensity in the fine fraction of the sediment, composed of clay and silt with particle sizes below 63 µm [13], generally by the metalloids associated with the minerals that had been mined. To determine this impact, the measured contents are compared with the geochemical background values and with the maximum allowable levels established for the regulations of the region and/or country using statistical methods and contamination indices [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the presence of OC in Corbicula in freshwater [8][9] [10] meanwhile other studies have recorded the concentration of OC in the lake waters [11]. Because of their relatively sedentary lifestyle [12] and easy to collect [10]., Corbicula could be an useful bioindicator for monitoring OC. The goal of our study was to determine the level of organochlorine residues in surface water and the mussel Corbicula sumatrana of Lake Singkarak.…”
Section: Introductionmentioning
confidence: 99%